If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x = 5x + -8x + -12 Reorder the terms: 6 + -6x = -12 + 5x + -8x Combine like terms: 5x + -8x = -3x 6 + -6x = -12 + -3x Solving 6 + -6x = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + -6x + 3x = -12 + -3x + 3x Combine like terms: -6x + 3x = -3x 6 + -3x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + -3x = -12 + 0 6 + -3x = -12 Add '-6' to each side of the equation. 6 + -6 + -3x = -12 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = -12 + -6 -3x = -12 + -6 Combine like terms: -12 + -6 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| X+8.1=3.9 | | 33(3m-2)=2(3m+3) | | 1+7x=-3+121 | | 12=3x+27 | | 45=3x+7 | | 3(3n-1)=(4n+2)+8 | | 16x^2+30x-x^3=6x-9-x^3 | | -1+(-3)=x | | 6x+28=-9x-2 | | 4+20x-20=5-10x+5 | | 7t-4=10t-14 | | 15=2y-12 | | 5x+6-12x=-12 | | -14-8=e | | 35+35+x=180 | | 5-(3n-4)=3(n+2) | | 6a-2(a-3)=-12 | | 19=-3k-5 | | 4(1)-7y=15 | | 3x-4=2-4 | | 3(x+7)+2=2x+2(3x-1) | | 7p-36=-4(-6p-8) | | 6-4+5*11= | | -2u^2-7u-5=0 | | -3(5-b)= | | 2(-2x+4)=-8 | | 4x^3+13x^2+4x-12=0 | | -6x+7x+6=18 | | 2(+3)+4s-5+s=148 | | 4(5+4)-10=2(9+f)-6 | | 12x-4=5x+66 | | 4(x+5)-6=6x-2(-5+x) |